Extrapulmonary manifestations of coronavirus disease (COVID-19): current status (a literature review) - Riabokon, O. V.; Pak, К. А.; Riabokon, Yu. Yu.; Furyk, О. О.; Cherkaskyi, V. V.; Рябоконь, Олена Вячеславівна; Пак, Катерина Анатоліївна; Рябоконь, Юрій Юрійович; Фурик, Олена Олександрівна; Черкаський, Володимир Васильович (Запорізький державний медичний університет, 2022)
The aim of the study is to analyze the literature data on modern views concerning extrapulmonary manifestations of coronavirus disease (COVID-19). Based on the analysis of current publications, the article analyzes the clinical manifestations of coronavirus disease (COVID-19) as a multisystem disorder with two main types of clinical manifestations, namely pulmonary and extrapulmonary. Determining pathogenetic mechanisms of extrapulmonary symptoms are, on the one hand, the tropism of SARS-CoV-2 to ACE2 receptors, expressed not only by alveolar epithelial type II cells, but also by cells of the heart, nervous system, vascular endothelium, small and large intestine, basal layer cells of the epidermis, cells of endocrine organs, etc., and on the other hand, immune-dependent mechanisms, in particular the development of “cytokine storm”. It is shown that the spectrum of extrapulmonary manifestations of COVID-19 is very wide, and clinical manifestations are characterized by significant polymorphism. Extrapulmonary symptoms of COVID-19 were analyzed considering the organs of the gastrointestinal tract, nervous, cardiovascular and endocrine systems, skin and others. Attention is drawn to a certain association between definite extrapulmonary manifestations and the severity of COVID-19 course. Мета роботи – проаналізувати відомості фахової літератури щодо сучасних уявлень про позалегеневі прояви коронавірусної хвороби (COVID-19). На підставі аналізу сучасної наукової літератури проаналізували клінічні прояви коронавірусної хвороби (COVID-19) як мультисистемного захворювання з двома основними типами клінічних проявів: легеневими та позалегеневими. Визначальні патогенетичні механізми виникнення позалегеневої симптоматики, – тропізм SARS-CoV-2 до рецепторів ACE2 (є не лише на альвеолярних клітинах ІІ типу, але й на клітинах серця, нервової системи, ендотелію судин, тонкого і товстого кишечника, клітин базального шару епідермісу, клітинах органів ендокринної системи тощо), а також імунозалежні механізми, зокрема розвиток «цитокінового шторму». Показано, що спектр позалегеневих проявів COVID-19 дуже широкий, а клінічні прояви вирізняються істотним поліморфізмом. Проаналізували позалегеневу симптоматику COVID-19 з боку органів шлунково-кишкового тракту, нервової, серцево-судинної та ендокринної систем, шкіри тощо. Звернули увагу на певну асоціацію окремих позалегеневих проявів із тяжкістю перебігу COVID-19.
Позалегеневі прояви коронавірусної хвороби (COVID-19): сучасний стан питання (огляд літератури)
Riabokon O. V. - ORCID ID: 0000-0002-7394-4649; Pak K. A. - ORCID ID: 0000-0002-2286-6919; Riabokon Yu. Yu. - ORCID ID: 0000-0002-2273-8511; Furyk O. O. - ORCID ID: 0000-0002-5196-7698; Cherkaskyi V. V. - ORCID ID: 0000-0003-2959-8803.
Keywords: coronavirus disease COVID-19; viral infection; extrapulmonary manifestations; коронавірусна хвороба COVID-19; вірусна інфекція; позалегеневі прояви